Botulinum Toxin in Children and Adolescents—A Comprehensive Review of Clinical Applications - Marko Bašković; Vedrana Nikić Čižmek; Jana Buzuk; Bianka Dujić; Danijela Jurić; Kristina Jurković; Karla Pehar; Sara Vuković (Toxins, 2026)
Botulinum toxin, once known only as the cause of botulism, has become a versatile therapeutic agent whose use in children now extends across many medical and surgical specialties. This narrative review synthesises the clinical use of botulinum toxin in patients up to eighteen years of age. We describe its pharmacology, the non-interchangeable commercial preparations, and the weight-based dosing and safety principles specific to childhood, then examine its applications by organ system. Gastrointestinal uses include functional constipation and internal anal sphincter achalasia, persistent obstruction after surgery for Hirschsprung disease, anal fissure, and achalasia. Urological uses centre on neurogenic and idiopathic detrusor overactivity and on sphincter-directed injection for dysfunctional voiding. Neurological uses are dominated by cerebral palsy spasticity and, on considerably weaker evidence, dystonia, while head and neck uses include sialorrhoea, congenital muscular torticollis, and strabismus. We also address neonatal brachial plexus palsy together with hyperhidrosis and aesthetic use in adolescents. The evidence supporting these uses is markedly uneven. Randomised controlled trials exist for only a small number of paediatric indications, chiefly spasticity in cerebral palsy, neurogenic detrusor overactivity, and chronic sialorrhoea, whereas most remaining applications rest on observational cohorts, small case series, or extrapolation from adult practice, and we grade the certainty of evidence separately for every indication. Only a few indications are formally approved, and most remain off-label, though increasingly supported. Botulinum toxin is a reversible and generally safe adjunct, but rigorous paediatric trials are still needed.